Variation of the Photon Attenuation Coefficients of Pumice Concrete in Different Chemical Media - Akkurt, I.; Akyildirim, H.; Karipçin, F. (Asian Journal of Chemistry, 2013)
As the radiation has started to be used in a variety of different fields after the development of technology, its shielding became one of the main research in physics. This is because of its hazardous effect on human cell. Different types of material including lead or concrete can be used to shield hazardous radiation. On the other hand the radiation shielding properties of those materials can be deformed by outer effect. The effect of chemical media on the radiation shielding properties of concrete has been investigated. The linear attenuations have been measured at 662, 1773 and 1332 keV for 6 month period. The measurement has been performed using g-spectrometer contains a NaI(Tl) detector and 16k channel MCA. It was found that the chemical media decreased linear attenuation coefficients of the pumice concrete.